A New Comprehensive Methodology for Postfault Operation of Three-Phase Induction Motor Drives - Salvatore Pollaccia; Massimo Caruso; Antonino Oscar Di Tommaso; Rosario Miceli (IEEE Open Journal of Industry Applications)
This article presents a novel fault-tolerant control (FTC) strategy for three-phase induction motor drives designed to maintain adequate operation during a fault occurring on either the electrical machine or the power converter sides. The proposed FTC ensures uninterrupted operation through software and hardware reconfigurations, which are specifically related to the fault type, leveraging a flexible machine and power devices fault-tolerant inverter topology. The system employs modified voltage references and asymmetric transformation matrices to adapt to inverter or motor faults while maintaining balanced operation and reduced torque, flux, and speed oscillations. Simulation and experimental results demonstrate the effectiveness of the proposed strategy in restoring operational integrity with limited performance degradation, highlighting its flexibility and suitability for critical industrial applications.